The “good taste” between the quantitative and qualitative model. Relevant social groups in Mendoza viticulture (1960-1990) - Cicirello, Emmanuel (Universidad Pedagógica y Tecnológica de Colombia, 2024)
In the province of Mendoza, specifically since the 1960s, public and privateeconomic policies were established that could be considered the origins of the technologicalchange that consolidated the wine restructuring in 1990. The quantitative production modelthat marketed common high-yield grapes and wines was affected by a global transformationof the wine market, the creation of institutions to control the authenticity of wines, the dropin consumption, and the impact of a prolonged and deep crisis of overproduction (1978-1990). These aspects stimulated the reorientation of some producers towards the international market and the “quality” paradigm, based on fine grapes and wines. They are strategies of Relevant Social Groups (public and private) that established as an innovation the export of fine wines associated with “good taste” as a solution to the crisis of overproduction.